Оптимизация процесса колебаний балки - Копец, М.М. (Проблемы управления и информатики, 2017)
Розглянуто лінійно-квадратичну задачу оптимального керування процесом коливань балки. Для даної задачі оптимізації отримано необхідні умови оптимальності. Аналіз цих умов дав можливість вивести систему інтегро-диференціальних рівнянь Ріккаті, розв’язок якої подано в замкненому вигляді. Consideration in given to the linear-quadratic optimal control problem of the process of a beam vibrations. For a considered optimization problem the necessary conditions of optimality are received. The analysis of these conditions has given the chance to deduce the system of Riccati integro-differential equations which solution is presented in closed form.